A Buddhist Wise Way to Decrease Unwholesome Roots in Daily Life - เรียงแหลม, แม่ชีสุนันทา (Journal of Buddhist Studies Chulalongkorn University, 2015)
The study, “A Buddhist Wise Way to Decrease Unwholesome Roots in Daily Life,” described unwholesome roots and to decrease them in the context of Buddhism. The study indicated that the unwholesome roots are Lobha (greed), Dosa (hatred), or Kodha (anger), and moha (delusion). Dhammas as a wise way to decrease Lobha are (1) practice of mind meditation, (2) donation, (3) moral shame, (4) moral dread, and (5) right means of livelihood. Dhammas as a wise way to decrease Dosa and Kodha are (1) precept observance, (2) loving, kindness and compassion, (3) tolerance, (4) taming, and (5) non-anger. Dhammas as a wise way to decrease Moha are (1) mental developments which are tranquillity development and insight development, (2) investigation, (3) calm and peace, (4) mindfulness, (5) wisdom, (6) concentration, (7) reasoned attention, (8) truth and investigation, (9) non-negligence, and (10) great learning.